María Jesús Zamora Calvo (ed.). Brujas de cine. Madrid: Abada Editores, 2016. - Arribas Rodríguez, Haydé (Cuestiones de Género: de la igualdad y la diferencia, 2017)
Brujas de cine. Autora: María Jesús Zamora Calvo (ed.) Editoras: Zamora Calvo, María Jesús. Madrid: Abada Editores, 2016